Penggunaan Bahasa Gaul Remaja Jakarta Selatan (Jaksel) pada Kanal Youtube Podcast Kesel Aje - Ribowo, Erik Prastiyo; Iswatiningsih, Daroe (Logat: Jurnal Bahasa Indonesia dan Pembelajaran, 2023)
The language used by teenagers in South Jakarta (Jaksel) is unique, because many of the vocabulary used is a blend of Indonesian and foreign languages. The formulation of the problem in this research is, (1) what is the form of South Jakarta youth slang found on the Kesel Aje Podcast YouTube channel?, (2) what is the meaning of South Jakarta youth slang on the Kesel Aje Podcast YouTube channel?, (3) what is the function from South Jakarta youth slang vocabulary?. The method used in this study is descriptive qualitative by describing the use of slang used by Oza Rangkuti on the Kesel Aje Podcast YouTube channel. The data collection technique is in the form of observing and noting. The data is described qualitatively according to the pattern of formation, meaning, and function. The data in this study were obtained from the results of data collection on nine videos uploaded on the Kesel Aje Podcast YouTube channel. The results of this study found six formation patterns in slang, namely, abbreviations consisting of 20 data, acronyms 7 data, compound words 6 data, puns 7 data, code mixing 6 data, absorption from foreign languages 16 data. Vocabulary in slang is used to establish communication between speakers and speech partners, to give terms to things that are done, as well as to express the feelings or thoughts of speakers.